Evaluation of thermal comfort criteria of an active chilled beam system in tropical climate: A comparative study. (November 2018) - Azad, Abdus Salam; Rakshit, Dibakar; Wan, Man Pun; Babu, Sushanth; Sarvaiya, Jatin N.; Kumar, D.E.V.S. Kiran; Zhang, Zhe; Lamano, Adrian S.; Krishnasayee, Krithika; Gao, Chun Ping; Valliappan, Selvam; Goh, Alice; et al.
Abstract: Air-conditioning systems are employed to provide thermal comfort inside buildings. Therefore, several air-conditioning and mechanical ventilation (ACMV) systems have been tested and applied in different climates. Chilled beam systems are a new addition to it and have been in the application in Europe and North America since last two decades. In the present study, comparative performance of active chilled beam (ACB) system with conventional fan coil unit (FCU) system has been appraised in regards to thermal comfort for the tropical region of Singapore. Experiments were carried out in a simulated office building with approximately 80% glazed area under real environmental conditions. Room air temperature, air velocity, mean radiant temperature (MRT) and relative humidity which are important thermal comfort parameters were measured in perimeter zone inside the cells and assessed. It was perceived that the ACB system was providing acceptable thermal comfort as per the standard of SS 554. General thermal comfort has been assessed based on an index of PMV-PPD model and graphical method. With regard to the local thermal discomfort: indices of air draught, vertical air temperature difference (VATD) and radiant temperature asymmetry have also been evaluated. The entrance of solar radiation through window façade may have a significant impact on the asymmetry of the radiant field and can enhance thermal discomfort of the occupants. Therefore, in the study radiant temperature asymmetry has been calculated extensively. The results show that ACB system yields satisfactory thermal environment as per ISO 7730 standard and sometimes performs even better than conventional FCU system. Highlights: Comparative performance analysis of conventional FCU and ACB system with regard to thermal comfort. Assessment of general thermal comfort criteria based on PMV-PPD model and Graphical method. The comfort zone has been proposed to assess the data points using graphical method for tropical Singapore. Assessment of local thermal comfort criteria based on air draught, VATD and radiant temperature asymmetry. Extensive analysis of the impact of solar radiation on the asymmetry of radiant field.